2015
DOI: 10.5665/sleep.4576
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Assessment of the Association of Polysomnographic Indices with Blood Pressure: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Our results support the use of a currently recommended apnea-hypopnea index definition as a marker of blood pressure risk and indicate that measurement of limb movements with arousals is also independently associated with diastolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
2
36
0
2
Order By: Relevance
“…However, both systolic and diastolic blood pressures were significantly higher in patients with OSAS and PLM. In their 2014 study, Dean et al (12) reported that PLM (PLMI ≥5) was associated with higher diastolic blood pressure irrespective of AHI. The presence of PLM in patients with OSAS may be a factor of increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both systolic and diastolic blood pressures were significantly higher in patients with OSAS and PLM. In their 2014 study, Dean et al (12) reported that PLM (PLMI ≥5) was associated with higher diastolic blood pressure irrespective of AHI. The presence of PLM in patients with OSAS may be a factor of increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are growing numbers of reports that suggest PLM as a novel risk factor in hypertension, cardiovascular, and cerebrovascular disorders (10,11). A recent study found a relationship between PLM and elevated diastolic blood pressure, irrespective of the apnea-hypopnea index (AHI) (12). PLM has also been reported to be a component of chronic diseases including congestive heart failure, chronic renal failure, Parkinson's disease, and sleep apnea (11).…”
Section: Introductionmentioning
confidence: 99%
“…The Multi-Ethnic Study of Atherosclerosis (MESA) concluded that OSA is a risk marker for increased blood pressure, whereas limb movements with arousals were independently associated with increased diastolic blood pressure. 8 In the current study, patients with significant PLMS had higher arterial stiffness at baseline, overnight, and in the morning, compared to ageand BMI-matched controls, and were generally comparable to those of patients with moderate/severe OSA. These findings may reflect the importance of PLMS in the development of CVD but also the applicability of using a validated marker of large artery stiffness, SI DVP , in large-scale studies through conventional pulse oximetry recordings, even without the utilization of commercial devices or sophisticated algorithms.…”
mentioning
confidence: 74%
“…8,9,11,27 Although conventional methods of measuring large artery stiffness would not be applicable during an overnight sleep study, new validated methods provide this option. SI DVP derived from photoplethysmography shares the same principles as pulse oximetry, allowing for overnight analysis in patients with various sleep conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation